The value of the family in Islamic law - Mukhitdinov, Rashid; Baizak, Maksat (Eurasian Journal of Religious Studies, 2019)
Society is made up of people. And the social, economic and spiritual prosperity of society is directly connected with every family life. The concept of family is not the only topic that can be addressed only in the field of Islamic law. The meaning of the concept of family is clearly stated in the texts of the Quran and Hadith. During the article, the main goal is to present the family value through the interpretation of religious texts and the hermeneutic analysis of scholars. Because the determination of the intentions of sacred texts influences religious law. Also on the subject of marriage may affect the concept of the concept of family.